The Mixed Arbitral Tribunals, 1919-1939 An Experiment in the International Adjudication of Private Rights - Fabri, Hélène Ruiz; Erpelding, Michel (Studies of the Max Planck Institute Luxembourg for International, European and Regulatory Procedural Law, 2023)
The creation of 39 Mixed Arbitral Tribunals ('MATs') was a major contribution of the post-World War I peace treaties to the development of international adjudication. With over 90 000 claims handled, the MATs were the busiest international courts of the interwar period. Moreover, in a departure from most other international courts and tribunals at that time, they allowed individuals to file claims against sovereign states before them. After 1945, they inspired the creators of the European Court of Justice before disappearing into quasi-oblivion. Relying on legal and historical research, including new archival findings, this volume is specifically dedicated to these pioneering institutions.